As iniciativas e experiências em agroecologia como estratégia de desenvolvimento local em um assentamento de reforma agrária - Barcellos, Sérgio Botton (Mundo Agrario.)
This paper searches to understand which disputes and conflicts are around the consolidation of agroecology as one of the alternatives and initiatives of local development in a land reform settlement. Thus, this paper, which consists of one of the results presented in the author´s dissertation, aims to identify the disputes and conflicts that occur among local initiatives related to agroecology. Santa Rosa settlement is located in one of the densest areas in relation to rural settlements in Rio Grande do Sul (RS) State. The research sources used to collect data and references to this paper were obtained in: researched bibliography in the writing of the author's dissertation; academic articles; and perceptions from the author's experiences in some land reform settlements. In this research it was considered that initiatives and actions in agroecology in the studied settlement can be strategic to make the social relations potential to the occurrence of experiences in local development different from those that occur alongside agribusiness.